Perception of Operators on Waste Management Systems in Desalination Plants in the United Arab Emirates - PRADEEP KUMAR, V. N (UNimas, 2023)
The technique of desalinating saltwater is one of the most practical ways to meet the growing need for freshwater in the Gulf countries, especially in the United Arab Emirates (UAE). Desalination offers great benefits in terms of the economy, society, and health; however, there are also negative effects on the environment because of uncontrolled waste disposal. The study aims to determine the perception of operators on waste management systems in desalination plants in the UAE. This study adopted a descriptive research design for collecting data about the impact of unregulated wastewater management and types of unregulated wastes using naturalistic observation and survey. The quantitative data was collected from the respondents using structured and close-ended questionnaires with a 4-point Likert scale. A simple random sampling method was used for selecting respondents in desalination plants. About 150 respondents were included in the study to get their perception of existing control measures and the development of innovative ideas or technology to control the brine impact and contribution of desalination plants to the development of waste management systems in the UAE. Data analysis was done using statistical tools like Chi-square. The results of this study showed that solar power plants benefit the UAE's people and economy. It was also observed that UAE desalination plants kept on trying new techniques like reverse osmosis (RO) and electro dialysis (ED) to reduce the levels of waste production and safeguard the natural surroundings. Hence, UAE desalination plants must adopt proper techniques and waste disposal methods to dispose of harmful brine, which will help preserve and safeguard the environment. It was found that the UAE is taking initiatives to treat and regulate brine discharge from desalination plants in order to provide citizens with safe and clean drinking water. However, the rejected brine and other waste liquids have a negative impact on the marine ecosystem.